The National Recovery Administration - Mason, Edward S. (Quarterly Journal of Economics, 1935)
Journal Article The National Recovery Administration Get access Edward S. Mason Edward S. Mason Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 4, August 1935, Pages 668–679, https://doi.org/10.2307/1885404 Published: 01 August 1935